2007
DOI: 10.1016/j.febslet.2007.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of T‐cell receptor signalling 1 and 2 differentially regulate endocytosis and signalling of receptor tyrosine kinases

Abstract: Suppressor of T-cell receptor signalling 1 and 2 (Sts-1 and 2) negatively regulate the endocytosis of receptor tyrosine kinases. The UBA domain of Sts-2 and SH3-dependent Cbl-binding are required for this function. Sts-1 and -2 also possess a PGM domain, which was recently reported to exhibit tyrosine phosphatase activity. Here, we demonstrate that the PGM of Sts-1, but not of Sts-2, dephosphorylates the EGFR at multiple tyrosines thereby terminating its signalling and endocytosis. In contrast to Sts-2 the UBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
(39 reference statements)
3
32
0
Order By: Relevance
“…Immunofluorescence staining is consistent with these results, indicating that TULA is primarily seen in the perinuclear area of the cytoplasm and that this staining demonstrates a diffuse/speckled pattern (7,8,14,15). Immunofluorescence staining of TULA-2 exhibited, likewise, the speckled/ diffuse intracellular localization of this protein in the cytoplasm (7,16).…”
Section: Protein Structure and Protein-protein Interactions Of Tulasupporting
confidence: 72%
“…Immunofluorescence staining is consistent with these results, indicating that TULA is primarily seen in the perinuclear area of the cytoplasm and that this staining demonstrates a diffuse/speckled pattern (7,8,14,15). Immunofluorescence staining of TULA-2 exhibited, likewise, the speckled/ diffuse intracellular localization of this protein in the cytoplasm (7,16).…”
Section: Protein Structure and Protein-protein Interactions Of Tulasupporting
confidence: 72%
“…TULA-2, also termed p70, STS-1, or UBASH3B, has been shown to be an active protein-tyrosine phosphatase (PTP) 2 (15)(16)(17) capable of suppressing receptor signaling in T lymphocytes (1,7,9,15), mast cells (18), osteoclasts (8), and platelets (6,19,20).…”
mentioning
confidence: 99%
“…The ability of TULA-2 to suppress T-cell receptor signaling depends on its phosphatase activity (6). Previous studies have indicated that TULA-2 dephosphorylates various Tyr(P) proteins, in particular protein-tyrosine kinases of the Syk and Src families, and demonstrates a certain degree of discrimination between them in in vitro assays (6,7,13). These observations raise several important questions about the TULA enzymes.…”
mentioning
confidence: 87%